2016
DOI: 10.1038/jes.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A exposure and children’s behavior: A systematic review

Abstract: Bisphenol A (BPA) is an endocrine disrupting chemical used to synthesize polycarbonate plastics and epoxy resins. Previous research suggests that exposure to it can alter children's behavior. The objective of this study is to conduct a systematic review of the existing literature, examining associations between prenatal and childhood BPA exposure and behavior in children up to 12 years of age. We searched electronic bibliographic databases (MEDLINE, PubMed, EMBASE, PsycINFO, CINAHL, and ERIC), reference lists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 60 publications
4
76
0
1
Order By: Relevance
“…To overcome this limitation, further longitudinal or quasi-experimental studies are required. In addition, previous studies for the association between BPA exposure and children's behavior have reported differential associations with children's behavior of the prenatal and childhood exposure to BPA [19]. Thus, the longitudinal study including the regular assessments of BPA exposure from prenatal period to childhood is warranted to confirm the present findings.…”
Section: Limitationssupporting
confidence: 67%
See 2 more Smart Citations
“…To overcome this limitation, further longitudinal or quasi-experimental studies are required. In addition, previous studies for the association between BPA exposure and children's behavior have reported differential associations with children's behavior of the prenatal and childhood exposure to BPA [19]. Thus, the longitudinal study including the regular assessments of BPA exposure from prenatal period to childhood is warranted to confirm the present findings.…”
Section: Limitationssupporting
confidence: 67%
“…However, there were no significant associations between BPA levels and scores on any subscales of the K-ARS or BASC-2 in girls. No previous studies have reported such sex-based differences, although some have identified significant associations between childhood BPA exposure and behavioral problems in both sexes [19].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interactions with diet may explain some of the inconsistencies in the BPA literature regarding effects on brain and behavior (93, 95). Nevertheless, linkages between developmental BPA exposure and an anxiogenic phenotype have repeatedly been shown in dozens of studies using a variety of animal models and human populations (representative examples include (62, 91, 93, 96100)). Acceptance of this outcome by the risk assessment community has been tentative because the causal mechanism(s) remains unclear (94).…”
Section: Bisphenol a (Bpa)mentioning
confidence: 99%
“…Exposure to bisphenols is associated with several neurological dysfunctions comprising memory and cognitive impairments, including aggression, hyperactivity, anxiety, depression, autism, and neuroinflammation. Children are more prone to bisphenol exposure, and even low concentrations (≤100 µM) are toxic to brain development in both prenatal and childhood stage [89,[121][122][123][124][125]. Exposure to BPA in the first trimester of pregnancy is associated with sleep-related problems in preschool children [80].…”
Section: Neurotoxicitymentioning
confidence: 99%